Sky Commons as a basis to explore the touristic potential of the Alqueva área (Portugal) - Rodrigues, Áurea (2021)
This paper analyzes the use of an unpolluted night sky as the basis for the differentiation of a rural tourism destination. As it has been pointed out in other studies the use of the commons as part of the tourism offer may lead to situations of overuse and pollution. In the present case it is shown that by having awareness of the tourism potential of this common resource, stakeholders of the Alentejo Region joined efforts to mitigate all the sources of pollution. A resource that was being neglected has become in the center of preservation policies of local public authorities of this region.